Contemporary advertising - Arens, William F; Weigold, Michael F.; Arens, Christian (New York McGraw - Hill, 2009)
Contents: advertising perspectives; crafting marketing and advertising strategies; creating advertisements and commercials; using advertising media; integrating advertising.
Includes index
Keywords: Quan hệ công chúng